Installation of Nationalism Attitude in the Thematic Learning of Class IV Students of SD Negeri Kartamulia, District of Madang Suku I - Andreansyah, Akbar; Idris, Muhamad; Irawan, David Budi (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this research is to describe the teacher’s strategy in instilling an attitude of nationalism in the nation’s cultural diversity through thematic learning in class IV students of Kartamulia Elementary School, Madang Suku I District. The problem in this study is what is the teacher’s strategy in instilling nationalism in the nation’s cultural diversity through thematic learning in Class IV Students of Kartamulia Public Elementary School, Madang Tribe I District. This research method uses qualitative research methods. Data collection techniques used were interviews, observations, and documentation. This research gives the result that: 1). The teacher’s way of instilling an attitude of nationalism through thematic subjects for fourth graders at Kartamulia Elementary School includes habituation, example, giving contextual examples, and the use of media such as pictures of traditional houses, traditional art musical instruments and singing national songs. 2). The embodiment of nationalism in grade IV SD Kartamulia students can be seen from the behavior of self-sacrifice, love of the motherland, pride as an Indonesian nation, unity and oneness, obedience to regulations, discipline, courage, honesty, and hard work. 3). The causes of delays in instilling an attitude of nationalism include the limitations of learning media and the way in which learning material is delivered by teachers only through the use of media.